2012
DOI: 10.1111/jace.12098
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aluminum in Solution on the Dissolution of Amorphous Silica and its Relation to Cementitious Systems

Abstract: One of the most serious causes of degradation of concrete is the alkali–silica reaction. Amorphous silicates present in certain aggregates react with the alkaline pore solution of the concrete to form a gel, which absorbs water and swells, leading to the expansion of the concrete. It is known that the deleterious effects of ASR can be suppressed by the incorporation of supplementary cementitious materials in the concrete, but the mechanisms operating are not clear. In this article, we study a model system of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 30 publications
5
39
0
Order By: Relevance
“…• Reducing silica dissolution rate from aggregates, by Al adsorption on the surface of reactive silica and/or formation of a diffuse zeolite barrier [180][181][182]; • Reducing the pore solution pH by formation of C-A-S-H, which improves alkali binding capacity over C-S-H [183]; • Reaction with and consumption of portlandite to form calcium aluminate phases; • Reducing swelling of ASR gel; • Densifying pore structure, and reducing permeability of concrete.…”
Section: Role Of Aluminummentioning
confidence: 99%
See 1 more Smart Citation
“…• Reducing silica dissolution rate from aggregates, by Al adsorption on the surface of reactive silica and/or formation of a diffuse zeolite barrier [180][181][182]; • Reducing the pore solution pH by formation of C-A-S-H, which improves alkali binding capacity over C-S-H [183]; • Reaction with and consumption of portlandite to form calcium aluminate phases; • Reducing swelling of ASR gel; • Densifying pore structure, and reducing permeability of concrete.…”
Section: Role Of Aluminummentioning
confidence: 99%
“…Chappex and Scrivener [182,184] demonstrated that presence of aluminum in pore solution can limit the dissolution of silica from aggregates. Two potential mechanisms have been suggested to explain how Al may impact the dissolution of silica in alkaline environments.…”
Section: Role Of Aluminummentioning
confidence: 99%
“…Especially in the field of osmotic membrane separation, it has been noted that only small amounts of cations impurities may impose different deposition structures , Cob 2012. Moreover, there has been considerable speculation on the role of aluminium in aluminosilicate deposition (Chappex 2012, Iler 1976, Bergna 1994). …”
Section: Concentration Polarisation (Cp)mentioning
confidence: 99%
“…Several investigators have shown the inhibitory effect of Al(OH) 4 À on the dissolution of silicate materials in highly alkaline solutions (Bickmore et al, 2006;Chappex and Scrivener, 2012;Snellings, 2013). According to the authors, Al(OH) 4 À would co-adsorb with Na + on silanol sites and passivate the surface of silicate materials.…”
Section: Inhibitory Effect Of Al(oh) 4 -In the Solutionmentioning
confidence: 99%